The conflict between the West and the World of Islam: Causes and Dynamics in the Historical Dimension - Bobokhonov, Rakhimbek Sarkhadbekovich; Sledzevsky, Igor Vasilievich (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the problem of conflict / dialogue between the Western world and the world of Islam. The subject of the article is the factors that impede the dialogue of these worlds as two world civilizations, create cultural and political, cultural and historical conditions for the existence and sharpening of deep divergences between these civilizations, and in modern conditions of a transboundary, increasingly unstable and uncertain world - transfer these differences in the context of mutual claims and exclusivism in relation to each other. The purpose of the study is to identify the main historical causes and dynamics (historical stages) of the emergence and sharpening of the conflict between European and Islamic civilization: first between Islam and Christianity, and then – in Modern and Contemporary times - between Islam and the West. The following methods have been used: civilizational comparative studies, comparative religion, terminological analysis. The dominant versions of the history of the conflict between Islam and Christianity, Islam and the West are analyzed in the world and Russian science. The concept of the underlying factors of this conflict, due to the nature of both civilizations, the tense cultural and historical ties of Islam and Christianity, is proposed.